2012
DOI: 10.2478/v10103-011-0023-1
|View full text |Cite
|
Sign up to set email alerts
|

Earnings Management in Polish Companies

Abstract: This paper presents results of the investigation of a phenomenon known as "earnings management'' (EM) among the companies listed on the Polish stock market. The distribution of earnings per share (EPS) for the stocks around the threshold value of "zero" and the threshold of "recent performance" was analyzed in the period of years 1997-2010. Moreover, the changes of earnings for the stocks, which are suspected to manipulate their earnings, were also investigated. The results, which indicate asymmetric d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 17 publications
0
4
0
4
Order By: Relevance
“…For example, Wójtowicz [72], with a sample covering the first stage of the Polish stock exchange's development up to the crisis (1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007), concluded that companies manage earnings to a similar extent to their foreign counterparts. Subsequent research by Brzeszczyński, Gajdka, and Schabek [73] documented the desire of public companies in Poland during 1997-2010 to report positive profits. Czajor, Michalak, Waniak-Michalak [74] investigated whether economic conditions influence earnings quality.…”
Section: Earnings Quality Around Going Public: the Existing Evidencementioning
confidence: 99%
“…For example, Wójtowicz [72], with a sample covering the first stage of the Polish stock exchange's development up to the crisis (1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007), concluded that companies manage earnings to a similar extent to their foreign counterparts. Subsequent research by Brzeszczyński, Gajdka, and Schabek [73] documented the desire of public companies in Poland during 1997-2010 to report positive profits. Czajor, Michalak, Waniak-Michalak [74] investigated whether economic conditions influence earnings quality.…”
Section: Earnings Quality Around Going Public: the Existing Evidencementioning
confidence: 99%
“…Previous research focused mainly on earnings management (Callao et al, 2017). Companies operating in Poland have already attracted the attention of researchers (Brzeszczyński et al, 2012;Piosik & Strojek-Filus, 2013), and such managerial activity was also addressed by IPO studies (Lizińska & Czapiewski, 2018;Sosnowski, 2018). Although there is evidence that companies operating in the Czech Republic, Slovakia, Hungary (Siekelova et al, 2020;Valaskova et al, 2021;Durana et al, 2022), and Bulgaria (Krastev et al, 2021) undertake earnings management initiatives, and empirical studies have confirmed the use of upward earnings manipulation (Kliestik et al, 2021), knowledge on earnings quality is still relatively scarce.…”
Section: Introductionmentioning
confidence: 99%
“…In Poland, more than sixty models have been developed, mainly focused on manufacturing enterprises using multiple discriminant analysis (Gajdka & Stos, 1996;Mączyńska, 1994;Pogodzinska & Sojak, 1995). Brzeszczyński et al (Brzeszczyński, Gajda, & Schabek, 2012) and Welc (2011) investigated earnings manipulation by Polish companies, and concluded that Polish stock market companies perform manipulation with earnings. As investigated by Callao et al (2017), Poland is a pioneer in developing models of detecting earnings manipulation (with more than ten models) when considering the V4 countries.…”
Section: Methods Of Identifying the Manipulation Of Financial Stateme...mentioning
confidence: 99%